Outcomes-based performance management through measuring indicators: Collaborative governance for local economic development (LED) in South African municipalities - Kamara, Richard Douglas (Technium Social Sciences Journal, 2020)
Undoubtedly, there is a lag in the scholarships on performance outcomes of collaboration aimed at improving the system management and responsiveness to socio-economic issues in local government. Whilst most scholarships on collaborative governance in LED focuses on what we do (processes), some others research addresses the outputs in terms of the goods and services produced from the activities as well as the social outcomes. Very little discourse on collaboration addresses collaborative outcomes in LED. Put simply, we are acquainted with what collaborative actors do, but we know very little about the impact of collaboration on the system management and responsiveness to socio-economic issues within municipalities. Now the question is how do we know what to measure? The dearth in scholarship on how to assess collaborative outcomes in LED provide an impetus to present this paper as it helps to address the knowledge gap on LED and collaboration. The paper aims to present some innovative indicators which can be used to assess, monitor and review collaborative performance in LED, with special focus on the processes and outcomes of the collaboration. Using secondary sources, the paper argues the desirability and constraints of assessing performance outcomes in collaborative governance of development pathways in local municipalities. Moreover, the paper presents some criteria for selecting effective indicators used in measuring outcomes performance of collaboration. A synopsis of major determinants of effective outcomes in collaboration for LED is presented in the paper. Finally, the paper presents proposed innovative quantitative and qualitative indicators which can be used to assess, monitor and review collaborative performance in LED in local municipalities.